Determination of the fit growth curve model and relationships among growth parameters by nonlinear functions in Kaçkar hair goats - S. Yüksel; F. Yüksel; E. Sezgin (Archives Animal Breeding)
The objectives of this study are to identify a suitable mathematical model for determining the breeding strategies and describing the growth curve of Kaçkar hair goat based on data at birth, at 3 months of age, 6 months of age, 9 months of age, and 12 months of age using records of body weight (BW), body length (BL), height at withers (HW), and chest circumference (CC) from birth to 12 months of age. Data of 242 Kaçkar hair goats as part of the National Project on Conservation and Sustainable Utilization of Domestic Animal Genetic Resources, on one farm, were recorded during the years 2018–2021 and analyzed for estimating growth curve parameters. The growth models were compared using the Bayesian information criterion (BIC), Akaike's information criterion (AIC), adjusted coefficient of determination (<msubsup>Radj2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="8dc21212760d5260bdb085c5fc983c7c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="aab-68-497-2025-ie00001.svg" width="20pt" height="18pt" src="aab-68-497-2025-ie00001.png"/></svg:svg>), and root mean square error (RMSE) based on the parameters of the growth curve such as the asymptote for the size measured (A), rate of gain (b), and growth rate – constant of integration (k). For the Brody model, we estimated <msubsup>Radj2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="b92edb8028b05e7d3b68f8f390b2fc79"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="aab-68-497-2025-ie00002.svg" width="20pt" height="18pt" src="aab-68-497-2025-ie00002.png"/></svg:svg> for body weight, body length, height at withers, and chest circumference that was 86.0 %, 85.2 %, 84.9 %, and 85.3 % in males and 86.0 %, 78.8 %, 79.7 %, and 84.8 % in females, respectively. For the Von Bertalanffy model, we also estimated <msubsup>Radj2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="c8d4c6c0b328146608f33fd0bbf40c1e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="aab-68-497-2025-ie00003.svg" width="20pt" height="18pt" src="aab-68-497-2025-ie00003.png"/></svg:svg> for same parameters that were 87.6 %, 85.7 %, 87.5 %, and 87.1 % in males and 85.9 %, 78.3 %, 82.6 %, and 80.2 % in females, respectively. Among all used models, the Brody for females and Von Bertalanffy for males resulted in the smallest AIC, BIC, and RMSE values. As a result, growth curve models are valuable instruments for determining the profitable slaughter age, and they provide practical information on the rearing practices of both sexes of Kaçkar hair goats for meat production. Thus, it could be applied to rearing programs for early selection, enabling breeding strategies when needed.